Saving, Investment and Tax Planning by Government Employees - Laskar, H. R. (International Journal of Psychosocial Rehabilitation, 2018)
Savings are the amount of money that people save after paying for various expenses. An investment is a strategy that involves putting capital to work to increase its value in the future. Every individual has a right to avail of all the tax incentives that the Government provides. Planning and keeping accounts in a safe and secure government scheme will help minimize one’s tax liability and provide a better future. The study’s objective is to determine the level of awareness among the employees of the Assam Government regarding the various tax planning provisions available to them and to compare the tax planning provision used by Teaching and Nonteaching employees. The study finds that both Teaching and Nonteaching employees are highly concerned about Saving. Overall, the awareness level of nonteaching employees is very high. The study finds that employees are unaware of the various provisions that can help them reduce their tax liability. The study revealed that seventy-two percent of the respondents formulate their tax plans at the end of theirfinancial year. Seventy-nine percent of the respondents do seek the services of tax consultants for filing their tax returns. People were reluctant to disclose details related to their savings and investments. Therefore, generalizations of the findings will require further investigation.